ANALISIS PENGGUNAAN HURUF KAPITAL PADA KARANGAN DESKRIPSI SISWA KELAS V SD NEGERI 1 PEKANBARU - Rahayu, Santy Erica; Kurniaman, Otang; Fendrik, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: One of the problems in schools is the lack of attention from the teacher to the students' writings. This study aims to determine the ability to use capital letters in the essay description fifth grade students of SD Negeri 1 Pekanbaru. This research is qualitative descriptive. The sampling technique in this research is total sampling. The data collection techniques using the test write (compose) the direct method. Data analysis techniques to analyze the capitalization of 56 fabricated descriptions of students. The use of capital letters consists of 15 aspects, but researchers only use six aspects, such as capital letters used as the first letter of a sentence initial 63.80% (category enough), a capital letter is used as the name of the 62.08% (category enough), capital letters used the first letter of the name of 44.93% (poor category), capital letters used the first letters themselves geography 28.80% (very poor category), capital letters used the first letters the title essay of 75% (both categories ), and capital letters are used the first letters of the title of 43.19% (poor category). From the data analysis it can be concluded that the fifth grade students of SD Negeri 1 Pekanbaru have not been able to use capital letters in accordance with Enhanced Spelling. The average of result shown 52,98% (poor category). The highest percentage in the aspect of capitalization that is used the first letters of the title essay 75% (both categories) and the lowest percentage of aspects of the use of capital letters is used the first letters themselves geography 28.80% (very poor category).Key Words: Capitalization Capital, Narrative Description